Emissaries from the Holy Land: the Sephardic diaspora and the practice of pan-Judaism in the eighteenth century - Lehmann, Matthias B. (Stanford studies in Jewish history and culture, 2014)
Network of beneficence -- Agents of philanthropy : emissaries from the Holy Land and the communities of the diaspora -- Ideological foundations -- Solidarity contested : ethnic division and the quest for unity -- End of an era : the transformation of the philanthropic network in the nineteenth century -- Epilogue : pan-Judaism